An Administrative Support System for Digital Transformation of Small and Medium-Sized Enterprises in Vietnam - Nguyen Trung Tuan; Nguyen Manh Tuan; Le Ngoc Thanh (Foundations of Management)
Digital transformation (DX) is complex with many automated parts, underlying integrations and processes that need to fit all together. Tools to support the management of DX activities are, therefore, crucial for every business. However, there are just a few of such tools available these days that can help businesses with the DX management both effectively and comprehensively, but none of them was designed particularly for small- and medium-size enterprises (SMEs) of Vietnam. In this study, we will conduct an overview of recent studies on DX, methods and models for SMEs, and relevant research works regarding information support systems for the management of DX for SMEs. We then propose a novel administrative support system that not only addresses the shortcomings of the current state-of-the-art DX management systems but also meets the requirements of DX for SMEs in Vietnam. In addition to the system design and development, we also implement and benchmark the software product at 11 SMEs in Vietnam (and some results if any).